Investigation of physical, chemical and microbiological quality of grape and mulberry leathers sold in Elazig (In Türkiye) - Demir, Pelin; Patir, Bahri (Univ Federal Santa Maria, 2024)
The aim of this study is the determination some quality parameters of grape and mulberry pestils (leathers) sold in Elazig. For this purpose, a total of 45 fruit pestil samples, of which 23 were grape pestils and 22 were mulberry pestils, were analyzed for their physical properties, chemical properties, and microbiological characteristics. In grape and mulberry pestils, the average L* (lightness/darkness) values were 42.72 and 44.81, a* (redness) values were 10.29 and 9.07, and b* (yellow) values were 20.90 and 20.90, respectively. In grape and mulberry fruit pestil samples, the thickness values were 1.62 and 1.34, pH values were 3.82 and 4.75, acidity values (as citric acid) were 0.63 and 0.22%, a(w) values were 0.602 and 0.627, dry matter values were 68.78% and 72.99 %, ash values were 2.25% and 0.64%, insoluble ash values in 10% HCl were 0.20 and 0.29, and Brix values were 18.83 and 19.36, respectively. TMAB, coliform, Staphylococcus-Micrococcus, and yeast-mold counts were found to be 4.72 and 4.48, 1.30 and 1.89, 2.11 and 2.12, and 2.04 and 2.11 log(10) cfu/g, respectively, in all samples examined. In 14 of the samples (31.11%), the total number of mesophilic aerobic microorganisms was found to be >5 log(10) cfu/g. Escherichia coli and Salmonella spp. were not found in any of the samples. However, the samples were found to contain significant levels of yeast-mold. There was no difference between the groups in microbiological terms in statistical analysis (P > 0.05). According to the current study, there was no standard production and not enough hygiene rules were observed in the pestil production process in family businesses in Elazig. On the other hand, essential information was obtained on some physical, chemical and microbiological quality parameters of grape and blackberry pulps sold in markets and stores in Elazig.
Investigação da qualidade física, química e microbiológica de couros de uva e amoreira vendidos em Elazig (na Turquia)
Keywords: traditional product; grape; mulberry; fruit leather; quality parameters